2015
DOI: 10.1002/elps.201400446
|View full text |Cite
|
Sign up to set email alerts
|

Combined dielectrophoretic and impedance system for on‐chip controlled bacteria concentration: Application to Escherichia coli

Abstract: Abbreviations: Impedance analysis (IA), escherichia coli (E. coli), digital lock-in (DLIA), analog-to-digital converter (ADC), finite element method (FEM). 2 AbstractThe present paper reports a bacteria autonomous controlled concentrator prototype with a userfriendly interface for bench-top applications. It is based on a micro-fluidic lab-on-a-chip and its associated custom instrumentation, which consists in a dielectrophoretic actuator, to preconcentrate the sample, and an impedance analyser, to measure conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…This can be evidenced in the growing number of published articles and citations reflected in Web of Science (WOS). This emergent trend is also evident for bacteria detection and concentration ( Figure 1 ) since several research groups reported the simultaneous measure of the concentrated bacteria in a single piece of equipment [ 14 , 30 , 35 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…This can be evidenced in the growing number of published articles and citations reflected in Web of Science (WOS). This emergent trend is also evident for bacteria detection and concentration ( Figure 1 ) since several research groups reported the simultaneous measure of the concentrated bacteria in a single piece of equipment [ 14 , 30 , 35 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 73%
“…DEP uses a nontoxic electrical stimulation to induce a frequency-dependent dipole in cells [ 45 ]. The dielectrophoretic force is defined by Equation (1) [ 36 , 46 , 47 ]: where F concerns to the dipole approximation to the DEP force, refers to the permittivity of the medium surrounding the sphere, ω is the radian frequency of the applied field, R corresponds to the radius of the particle, r is the spatial coordinate, and E refers to the complex applied electric field. CM is the Clausius-Mossotti (CM) factor that is given by: where and are the complex permittivities of the medium and the particle, respectively, and are each given by = ε + σ /( jω ), where σ is the conductivity of the medium or particle, ε is the permittivity of the medium or particle, , and j is .…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibition of the antibiotic was measured by the positive DEP frequency response and the length of the bacteria. In addition, the interdigitated DEP electrodes combine with the impedance analyzer were used to measure the bacteria concentration [143]. As the trapped bacteria concentration increases, the impedance decreases.…”
Section: Dep Applications In Biomedical Sciencesmentioning
confidence: 99%
“…Microchip electrophoresis (ME) is a rapid analysis technique with low sample consumption as well as automated analysis process and has been widely applied for DNA analysis [21][22][23], bacterial detection [24][25][26][27], and protein analysis [28][29][30]. Ronen et al reported a fluorescent microfluidic platform for the analysis of HpaⅡ MTase activity based on methylation-sensitive endonuclease HpaⅡ [31].…”
mentioning
confidence: 99%